The Conceptual Framework in Examining the Influence of Relationship Competency on Small Firm Performance with the Mediating Role of Dynamic Capabilities (Journal of Business Management and Accounting, 2017)
This conceptual paper explains the link between relationship competency of entrepreneurs and small firm performance and the mediating effect of dynamic capabilities on the link. Existing research work have revealed the importance of relationship competency of the entrepreneurs and dynamic capabilities for small firm performance. To advance and elaborate the effect of relationship competency on small firm performance through the linking of dynamic capabilities is being suggested as a latest conceptual model from the perspective of theory. Therefore, this conceptual model supported by two theories namely, the resource based view (RBV) and dynamic capabilities view (DCV). An essential perspective is being presented by this latest conceptual model taking into consideration the background of entrepreneurial relationship competency, dynamic capabilities and small firm performance. Accordingly, for business accomplishments and advancement in managerial wisdom an essential factor for the progress and stability of small business enterprise is dependent on entrepreneurs who equip themselves with vital relationship competency and firm’s dynamic capabilities. Thus, the authors strongly recommend empirically testing of this conceptual model across various industries.